Determinação de tenacidade à fratura em cerâmicas pelo Método de Indentação Vickers - Bárbara, Iago Cordeiro Santa (Universidade Federal de São Carlos, 2025)
This work aimed to evaluate the Vickers indentation fracture toughness measurement method for ceramic materials, assessing its advantages and disadvantages. Initial tests were conducted on several ceramic test specimens with different geometries to verify the primary potential of the method, which does not require a specific sample geometry. The materials used were alumina (Al₂O₃), spinel (MgAl₂O₄), zirconia (ZrO₂), and magnesia (MgO). It was possible to compare different methods of sample mounting for the surface polishing stage before indentation, as well as to compare the advantages and disadvantages of using optical microscopy versus scanning electron microscopy for visualizing the indentations. Additionally, compositions of alumina (Al₂O₃), yttria with zirconia (15 mol% Y₂O₃-stabilized ZrO₂), and pure yttria (Y₂O₃) were used for testing. The purpose was to evaluate a potential toughening effect of zirconia in yttria by comparing these values with those of alumina. The samples were sintered at 1650°C for 3 hours and underwent the same surface polishing process before indentation. The hardness values obtained varied between these compositions but are consistent with the literature, being 12.2 ± 0.4 GPa for yttria with zirconia and 9.2 ± 0.4 GPa for pure yttria. The fracture toughness measurements were similar for the two yttria-based materials but were lower than those found in other literature studies, with the obtained results being on the order of 1.17 ± 0.05 MPa·m¹/². It was not possible to perform measurements for the alumina sample because surface cracks did not form under the different applied loads. Finally, several equations used for calculating fracture toughness were compared. It was concluded that Niihara's equation for the median crack system provided values that most closely approximated those found in the literature. Nevertheless, one of the disadvantages of the method is the number of equations that must be tested, as there is no certainty about which one is ideal without consulting reference values from the literature. However, it was determined that this methodology is practical and low-cost, enabling numerous measurements to be made in a short time. Furthermore, comparing results between samples allows for the verification of the presence or absence of toughening mechanisms, which were not observed in the produced samples.
Determination of fracture toughness in ceramics by the Vickers Indentation Method
Keywords: Tenacidade à fratura; Indentação Vickers; Cerâmica; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS